2022
DOI: 10.1039/d1nj04800g
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenation of butyl levulinate to γ-valerolactone over sulfonated activated carbon-supported SnRuB bifunctional catalysts

Abstract: The synthesis of γ-Valerolactone (GVL) from butyl levulinate (BL) hydrogenation over sulfonated activated carbon (SAC) supported SnRuB bifunctional catalysts was studied. These catalysts were characterized by ICP, nitrogen physisorption, XRD,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…In our previous study, the SAC-supported 20Sn1RuB catalyst showed the highest GVL yield of 83.1% from the BL hydrogenation reaction for 3 h in the cyclohexane solvent at 180 °C and 3 MPa H 2 . The coexistence of the acid site over the SAC support and SnRuB hydrogenation site was cognized as responsible for GVL formation.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In our previous study, the SAC-supported 20Sn1RuB catalyst showed the highest GVL yield of 83.1% from the BL hydrogenation reaction for 3 h in the cyclohexane solvent at 180 °C and 3 MPa H 2 . The coexistence of the acid site over the SAC support and SnRuB hydrogenation site was cognized as responsible for GVL formation.…”
Section: Resultsmentioning
confidence: 97%
“…The catalyst recyclability test for BL hydrogenation over the 20Sn1RuB/CBSA-SB catalyst was performed. The separation and recycling methods of used catalysts under exposure to air were the same as that in our previous report . As can be seen in Figure , the BL conversion and GVL yield showed a slight decrease from 93.8 and 87.5 to 86.6 and 83.9% in the former three cycles, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations